Arthroscopic findings after shoulder dislocation - Medenica Ivica; Radunović Aleksandar; Madžarac Dragan; Zorić Miodrag; Bokonjić Dubravko; Stojković Bratislav (Vojnosanitetski Pregled, 2009)
Background/Aim. Recurrent instability of the shoulder joint is frequently difficult to differentiate from diseased or injured rotator cuff or tendon of the forearm flexor (m. biceps brachii). Shoulder joint arthroscopy has been only recently introduced into instable shoulder joint lesion examination. The aim of this study was to present and analyze an arthroscopic finding on instable shoulder joint in order to determine causes and mechanisms of instability, as well as principles of surgical treatment. Methods. Arthroscopy of the shoulder joint was performed in 158 patients with at least one documented shoulder joint dislocation. These patients were divided into two groups. The group I included the patients with one to three dislocations, while the group II those with more than three dislocations. Preoperative diagnosis was based on anamnestic data and clinical examination using specific tests, and on the diagnosis of shoulder joint using radiography or computed tomography. Results. Out of the total number of the patients 138 (87.34%) had injury of the anterior patellar brim, 119 (75.32%) had failure of the anterior capsule, 126 (79.75%) had compressive cartilage injury of the posterior part of the head of the upper arm bone (Hill-Sachs lesion), 102 (64.56%) had insufficiency of glenohumeral tendon, 11 (6.96) had complete cut of the rotator cuff, 23 (14.56%) had injury of the posterior patellar brim, 12 (7.59%) had injury of the upper anterior-posterior patellar brim (SLAP). Conclusion. According to the obtained results it could be concluded that there is no a unique injury that leads to shoulder joint instability. It is necessary to point out to the significance of anamnesis and clinical examination in making diagnosis. Arthroscopic diagnostics is indicated in clinically unreliable findings as an additional method for determining operative treatment.